Asuhan Keperawatan Pada Ny. N Dengan CKD (Chronic Kidney Disease) Di Ruang Pejuang RSUD Bangkinang Tahun 2024 - Jihan Abadi; Muhammad Nurman (Excellent Health Journal, 2025)
Chronic renal failure (CKD) is a condition where there is a decrease in kidney function due to chronic and irreversible renal parenchyma with a glomerular filtration rate (LFG) < 60 mL / minute within 3 months or more, so that the body fails to maintain metabolism and electrolyte fluid balance, which causes uremia. The purpose of this study was to assess the implementation of nursing care for patients with CKD in the Pejuang room of Bangkinang Hospital in 2024. This research method uses a descriptive research design in the form of a case study. The subject of the case report is Mrs. N who is 24 years old with CKD in the Pejuang room of Bangkinang Hospital which was carried out for 3 days on June 12 to 14, 2024. Data obtained by interview, physical examination and supporting examination. At the time of assessment, the client felt a fever since a week ago accompanied by nausea and vomiting, the body felt weak, the appetite was reduced and the patient said there was pain in the solar plexus, accompanied by shortness of breath, headache. Researchers established the main problem with the nursing diagnosis of ineffective breathing patterns associated with neuromuscular. After three days of nursing implementation on the client, the problem was resolved. The researcher hopes that the writing of this case study report will serve as a reference in providing nursing care to patients with chronic renal failure.